THE EFFECT OF CAPITAL ADEQUACY RATIO AND LOAN TO DEPOSIT RATIO ON RETURN ON ASSETS AT PT. BANK MEGA, TBK. - andi sartika; Jeni Tiku Buana; Fakhruddin Kurnia M (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2022)
Abstract The purpose of this research is to know the effect of Capital Adequacy Ratio and Loan to Deposit Ratio on Return On Assets at PT. Bank Mega, Tbk. The type of data used is quantitative data. The data source used is a secondary data source. The analytical method used in this research is descriptive quantitative, multiple linear regression, correlation coefficient (r), coefficient of determination (r2), F test and t test. The results showed the value of the regression equation Y= - 5.685+0.183X1+0.060X2, the correlation value (r) was 0.989, the determination value (r2) was 0.979, the t-test b1 was 9.389>2.91999, this shows that Capital Adequacy Ratio has a positive and significant effect on Return On Assets and the t b2 test is 5.981>2.91999, this shows that Loan to Deposit Ratio has a positive and significant effect on Return On Assets. The results of the F test are 46.522>9.55, this indicates that Capital Adequacy Ratio and Loan to Deposit Ratio together have a positive and significant effect on Return On Assets at PT. Bank Mega, Tbk. Hypothesis accepted.   Keyword: Capital Adequacy Ratio, Loan to Deposit Ratio, Return On Assets